2021
DOI: 10.1063/5.0035926
|View full text |Cite
|
Sign up to set email alerts
|

Early-time symmetry quantifying with thin-shell capsule radiography for pulse shaped implosion

Abstract: To achieve ignition with high gain in inertial confinement fusion, precise symmetry control is one of the key issues to guarantee the PdV work converting into the inner energy efficiently and maximize the pressure of the hot spot. The shaped pulse is used to maintain a low adiabat of the shell. A longer pulse and more compressible shell require more rigorous symmetry control, especially the driven symmetry during the picket pulse and main pulse. A surrogate capsule with high Z materials is usually used for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…2 /P 0 drive asymmetry in the 2D capsule-only simulation and the model, we compare the percent R s P 2 /P 0 asymmetries vs the average R s extracted from the measured backlit images (Exp) in our previous backlit shell distortion experiment [18], the 2D simulated result (Simu_2D), and the model, as shown in figure 7. The estimated error of the experimental data includes both the accuracy of the measurement and the statistical uncertainty in the fitting process of the shell distortion [19]. It is found that the model result is in good agreement with both the experimental and the 2D simulated results.…”
Section: Using Thementioning
confidence: 58%
See 4 more Smart Citations
“…2 /P 0 drive asymmetry in the 2D capsule-only simulation and the model, we compare the percent R s P 2 /P 0 asymmetries vs the average R s extracted from the measured backlit images (Exp) in our previous backlit shell distortion experiment [18], the 2D simulated result (Simu_2D), and the model, as shown in figure 7. The estimated error of the experimental data includes both the accuracy of the measurement and the statistical uncertainty in the fitting process of the shell distortion [19]. It is found that the model result is in good agreement with both the experimental and the 2D simulated results.…”
Section: Using Thementioning
confidence: 58%
“…In this section, we apply the dynamic model to the acceleration phases of typical gas-fill capsule and layered DT capsule implosions with P 2 or P 4 drive asymmetries, and compare the P n mode amplitudes of v s and R s derived from the model, the 2D capsule-only radiation hydrodynamic simulations and available backlit shell distortion measurements. The angleaveraged ρR s (t), v s (t), and R s (t) in equations ( 13), ( 14), (18), and (19) were obtained from 1D multi-group radiation transfer (MGRT) code RDMG [31]. The 2D capsule-only simulations were performed using the 2D MGRT code LARED [32][33][34].…”
Section: Model Applications and Discussionmentioning
confidence: 99%
See 3 more Smart Citations